The global burden of chromoblastomycosis. - Daniel Wagner C L Santos (Public Library of Science (PLoS), 2021)
Background Chromoblastomycosis (CBM), represents one of the primary implantation mycoses caused by melanized fungi widely found in nature. It is characterized as a Neglected Tropical Disease (NTD) and mainly affects populations living in poverty with significant morbidity, including stigma and discrimination. Methods and findings In order to estimate the global burden of CBM, we retrospectively reviewed the published literature from 1914 to 2020. Over the 106-year period, a total of 7,740 patients with CBM were identified on all continents except Antarctica. Most of the cases were reported from South America (2,619 cases), followed by Africa (1,875 cases), Central America and Mexico (1,628 cases), Asia (1,390 cases), Oceania (168 cases), Europe (35 cases), and USA and Canada (25 cases). We described 4,022 (81.7%) male and 896 (18.3%) female patients, with the median age of 52.5 years. The average time between the onset of the first lesion and CBM diagnosis was 9.2 years (range between 1 month to 50 years). The main sites involved were the lower limbs (56.7%), followed by the upper limbs (19.9%), head and neck (2.9%), and trunk (2.4%). Itching and pain were reported by 21.5% and 11%, respectively. Malignant transformation was described in 22 cases. A total of 3,817 fungal isolates were cultured, being 3,089 (80.9%) Fonsecaea spp., 552 (14.5%) Cladophialophora spp., and 56 Phialophora spp. (1.5%). Conclusions and significance This review represents our current knowledge on the burden of CBM world-wide. The global incidence remains unclear and local epidemiological studies are required to improve these data, especially in Africa, Asia, and Latin America. The recognition of CBM as NTD emphasizes the need for public health efforts to promote support for all local governments interested in developing specific policies and actions for preventing, diagnosing and assisting patients.